Sunday Star, 19 April 2009 - Tan, Jacoline (Star Publications, 2009)
As Home Minister, Datur Seri Hishamuddin Tun Hussein is in charge of a ministry which carries all the hot political buttons and he has indicated that he is prepared to be as tough as it takes